Glucose-Derived Carbon Nanospheres as Flame Retardant for Polyethylene Terephthalate - Li, Jiaqian; Yang, Yaru; Xiao, Yunchao; Tang, Bolin; Ji, Yaming; Liu, Shuqiang (Frontiers in Materials, 2021)
To improve the flame retardant properties of polyethylene terephthalate (PET), glucose-derived carbon nanospheres (CNSs) were synthesized and introduced into PET matrix. The thermal property and flame retardancy of CNSs/PET composites were thoroughly investigated. Results showed that CNSs displayed good flame-retardant performance for PET. When blended with only 1.0 wt.% of CNSs, CNSs/PET exhibited a limiting oxygen index (LOI) of 26.3 and a vertical combustion class of V-2, and its peak-heat release rate (pk-HRR) was reduced by 41.6%. Importantly, the initial decomposition temperature and the maximum weight loss temperature of CNSs/PET were 52℃ and 199℃ higher than those of PET, respectively. Furthermore, a condensed phase flame-retardant mechanism appeared in CNSs/PET, which formed a dense and thermally stable protective char layer during combustion. Overall, this study disclosed the flame-retardant potential and possible mechanism of CNSs for polyesters, which would benefit the development of carbon-based materials and flame-retardant polymers.